Cyberwar and the Russian Federation: the usual suspect. (1st July 2010) - Tenreiro De Magalhaes, Sergio; Santos, Henrique M. Dinis; Dos Santos, Leonel Duarte; Jahankhani, Hamid
The evolution of the technology and the changes in the organisation and control of the critical infrastructures of nations are creating a new combat front. The cases studied in this paper are related to the attack to the information systems and services of Estonia, in April 2007, and Georgia, in August 2008, occurring at the same time as the conventional military operation executed by the Russian Federation's army in the South Ossetia. The Russian Federation has been repeatedly accused of this operations, but the data collected raises doubts and in the second case-study showed the existence of a poorly organised network, related to Russian criminal organisations, supporting the possibility of this being an instance of the Maoist concept of the 'People's war'. This paper will also show that, despite the unsophisticated resources used in most of the attacks and to promote them, the damages in the selected targets were considerable.